KESALAHAN SISWA DALAM MENYELESAIKAN SOAL CERITA PADA MATERI ARITMETIKA: SUATU PENELITIAN KUALITATIF BERDASARKAN PROSEDUR POLYA - Nedelan, Selviani S. D.; Tilaar, Anetha L. F.; Regar, Vivian E. (Jurnal Lebesgue : Jurnal Ilmiah Pendidikan Matematika, Matematika dan Statistika, 2024)
This research aims to describe the mistakes made by students when solving questions according to the Polya procedure. The type of research used is descriptive qualitative. The method used for data collection consisted of written tests and interviews. A written test was given to 18 students from class VIIC, which consisted of 4 descriptive questions; after that, from the results of the written test, three students were selected to be interview subjects. The interview process was selected based on ability, from those with high, medium and low ability. In this research, the stage used to analyze data is identifying error data according to the Polya procedure. This research shows the mistakes made by class VIIC students of SMP Negeri 11 Manado in solving story questions on Social Arithmetic material. Based on the Polya procedure in solving math story problems on social arithmetic material, it can be seen that the percentage of errors made by students most often occurs, namely errors in rechecking 40%, errors in completing planning 33.84%, planning solutions 30.76%, understanding the problem 26.15 %. Students do not write down what they know and are asked according to the question given, make mistakes in determining the mathematical model used and, do not write down the formula in solving the problem, make mistakes in determining the steps to solve the problem so that they experience errors incorrect calculations and the mistakes that are most often made students do not write down the final answer or are wrong in determining the final answer